Quantification of Pore Size and Movable Fluid Distribution in Zhangjiatan Shale of the Ordos Basin, China - Jing Xu; Yunjin Ge; Yonghong He; Renhai Pu; Linyu Liu; Kefeng Du; Hongjin Li; Xiao He; Liang Duan (Geofluids)
The Triassic Zhangjiatan shale in the Ordos basin, recognized as one of most promising shale oil and gas resources in China, is one example of medium-low-maturity lacustrine shale reservoirs wherein the pore network has been proven to be different from those of both conventional and high-maturity marine shale reservoirs. Here, we examine the quantitative characterization of pore size and movable fluid distribution of the Zhangjiatan shale reservoir. Eight shale core plugs were measured in a series of nuclear magnetic resonance (NMR) experiments to determine the pore structure and pore fluid transport during the processes of centrifuging and heating. The complete pore size distribution was obtained from the T2 spectrum by integrating NMR, high-pressure mercury intrusion, and nitrogen gas adsorption. The results show that the movable fluid saturation of Zhangjiatan shale is 19.47–33.02% and the capillary-bound fluid saturation is 14.53–27.62%, whereas the unrecoverable fluid saturation was 43.51–65.26%. The movable fluids are mainly detected in macropores and mesopores with a minimum pore size of 50.5–121.2 nm, while capillary-bound fluids are mainly found in small pores and some mesopores with a minimum size of 25.8–67.5 nm. Almost all unrecoverable fluids are in micropores and small pores. In contrast to high-maturity shale reservoirs, the Zhangjiatan shale shows a poor correlation between total organic carbon content and unrecoverable fluid saturation but a good correlation between clay minerals and unrecoverable fluid saturation, showing that most micropores are associated with clay minerals and the organic matter pores are less developed. This study provides an accurate determination of the pore size distribution and pore fluid typing of Zhangjiatan shale, which is of great significance for the development of high-quality but medium-low-maturity shale reservoirs in China.